Characteristics of pmma-grafted natural rubber polymer electrolytes / Yap Kiat Sen - Yap, Kiat Sen (2012)
The main focus of this work is to develop high conducting solid polymer electrolytes (SPEs). There are three polymer electrolyte systems in this project. Natural rubber (NR) grafted with 30 wt. % poly(methyl methacrylate) (PMMA) and designated as MG30 is used as polymer host and solution cast technique has been employed to produce sample films in this work. X–ray diffraction (XRD) studies have shown that all the samples prepared are amorphous and the morphology of the samples has also been investigated using scanning electron microscopy (SEM). Fourier transform infrared spectroscopy (FTIR) indicates complexation between component materials in the polymer electrolytes based on the changes in peak location and intensity as well as formation of new peaks. The conductivity of pure MG30 film is low, which is about 2.6 × 10–11 S cm–1 at room temperature. MG30 with 30 wt. % LiCF3SO3 salt (MG30L) exhibits the highest ambient conductivity of 1.69 x 10–6 S cm–1 in the single–salt system. Double–salt polymer electrolytes are prepared using different ratios of LiCF3SO3 and LiN(CF3SO2)2 with the total composition maintained at 30 wt. %. The maximum room temperature ionic conductivity is 1.46 × 10–5 S cm–1 exhibited from the sample MG15L15I consisting of equal ratio of the two salts. The ambient temperature ionic conductivity of plasticized polymer electrolytes increases to a maximum value of 3.65 × 10–4 S cm–1 with an activation energy of 0.11 eV upon addition of 10 wt. % PEG200 (MG30L–10P) to the MG30L sample. The ionic conductivity of all samples increases with increasing temperature following Arrhenius rule. The dielectric behavior was analyzed using dielectric permittivity and dielectric modulus of the samples. The dielectric constant of pure MG30 is ~ 1.86.